2016
DOI: 10.1007/s40093-016-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of municipal solid waste compost, peat, perlite and vermicompost on tomato (Lycopersicum esculentum L.) growth and yield in a hydroponic system

Abstract: Purpose An experiment was conducted to assess the ability of municipal solid waste compost (MSWC), peat, perlite and vermicompost (VC) to improve the growth of tomato (Lycopersicon esculentum L.), an important horticultural commodity, in hydroponic culture. Methods Organic matter, when used as a substrate, can affect tomato cultivar 'Grandella' plant growth. In this study, we studied the effect of MSWC, either composted by earthworms (VC), or in an uncomposted form, as well as conventional substrates peat and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
2
15
0
1
Order By: Relevance
“…If managed properly, organic waste material can be used to increase soil fertility and improve soil structure to promote root growth (Siddiqui and Akhtar 2008). Many studies have shown that root biomass (Montemurro et al 2007;Haghighi et al 2016); number of root tips (Guo et al 2016); root activity (Zhu et al 2002); and root length, surface area and volume (Guo et al 2016;Tian et al 2017) increase after the addition of organic waste. These findings are consistent with those of the current study (Figs.…”
Section: Effects Of Organic Materials Addition On Root Growthmentioning
confidence: 99%
“…If managed properly, organic waste material can be used to increase soil fertility and improve soil structure to promote root growth (Siddiqui and Akhtar 2008). Many studies have shown that root biomass (Montemurro et al 2007;Haghighi et al 2016); number of root tips (Guo et al 2016); root activity (Zhu et al 2002); and root length, surface area and volume (Guo et al 2016;Tian et al 2017) increase after the addition of organic waste. These findings are consistent with those of the current study (Figs.…”
Section: Effects Of Organic Materials Addition On Root Growthmentioning
confidence: 99%
“…soil fertility management (Weber et al 2014) and MSWM (Srivastava et al 2015). Application of MSW compost in agricultural land usually poses positive effect on the productivity of a wide variety of cropland vegetables (Warman et al 2009;Fagnano et al 2011;Papafilippaki et al 2015;Mkhabela and Warman 2005;Chrysargyris and Tzortzakis, 2015), and also in hydroponic system (Haghighi et al 2016). Mkhabela and Warman (2005) evaluated effect of MSWC on potatoes and sweet corn and found that this compost was a good source of P for both vegetables.…”
Section: Agricultural Utilization Of Msw Compostmentioning
confidence: 99%
“…Mkhabela and Warman (2005) evaluated effect of MSWC on potatoes and sweet corn and found that this compost was a good source of P for both vegetables. Recently, Haghighi et al (2016) conducted an experiment to assess the ability of MSWC to improve the growth of tomato under hydroponic system. The authors found that 25 % of MSWC added to hydroponic solution increased the numbers of fruits as compared with the control.…”
Section: Agricultural Utilization Of Msw Compostmentioning
confidence: 99%
“…Adamcova and Vaverkopa [16] found a high percentage of germination capacity of white mustard seed (Sinapis alba) are grown in pots were treated with MSWC. The growth of tomato in hydroponic culture was enhanced when MSWVC and MSWC were used [17]. The objective of this study to investigate the effect of media composition on growth of two varieties of Chrysanthemum.…”
Section: Introductionmentioning
confidence: 99%